Does the Chicago Safe Passage Program Reduce Reported Crime Around Elementary Schools? Evidence From Longitudinal, Geocoded Crime Data - Curran, F. Chris (Criminal justice policy review, 2019)
The Chicago Public School’s Safe Passage program is a large-scale intervention designed to improve the safety of students as they travel to and from schools. By placing hundreds of adult monitors on designated streets around schools, the program has the potential to reduce crime. This study evaluates Safe Passage’s impact on crime around primary schools during the 2013-2014 expansion of the program. Using longitudinal, geocoded crime data and a difference-in-differences and triple-difference methodology, this study finds suggestive, though not conclusive, evidence that Safe Passage may have contributed to lower crime on designated routes despite some increases in crime around designated “welcoming schools” during the 2013-2014 school year. Implications for the continued expansion of the program and further directions for research of the program are discussed.